0824 Improving Subjective Sleep Quality Measures Through Mindfulness Training in the Elderly: Preliminary Data from the Mindfulness Sleep Therapy (MIST) Study. (27th May 2020) - Perini, F; Foong Wong, K; Teng, J; Hassirim, Z; Lin, J; Leow, Z; Lee Henderson, S; Fan, Q; Lo, J C; Ong, J C; Doshi, K; Lim, J
Abstract: Introduction: Poor sleep is a modifiable risk factor for multiple chronic disorders. Mindfulness-based therapies potentially improve sleep by enhancing awareness and acceptance of internal and external experiences, thus reducing pre-sleep hyper-arousal. In this pre-registered, randomized controlled trial, we tested the effect of mindfulness-based treatment for insomnia (MBTI) on subjective sleep quality measures (Pittsburgh Sleep Quality Questionnaire, PSQI) in the elderly. Methods: Participants above 50 years old with sleep difficulties (PSQI ≥ 5) (mean (sd) age = 62.0 (6.35), 44 female) attended either an 8-week MBTI (N = 34) or sleep hygiene education and exercise program (SHEEP; N = 35). Before and after the interventions, we collected PSQI, insomnia symptoms and features measures (Pre-Sleep Arousal Scale, PSAS; Insomnia Severity Index, ISI; Dysfunctional Beliefs and Attitudes about Sleep, DBAS-30), mindfulness (Five-Facets Mindfulness Questionnaire, FFMQ), and mood and anxiety (Back Depression Inventory, BDI; State-Trait Anxiety Inventory, STAI). PSQI and PSAS (N = 26 to date) were collected at 6-month follow-up. Data were analysed with repeated-measures ANCOVA with group as a between-subject variable for the first 69 participants who completed the study. Results: We observed significant improvement across both groups for sleep measures (PSQI: F1, 67 =36.442, p <.01; PSAS-Cognitive: F1, 67 =12.664, p <.01; ISI: F1, 67 =36.442, p <.0; DBAS: F1, 67 =28.749, p <.01) and mood (BDI: F1, 67 =26.393, p <.01; STAI-State: F1, 67 =4.608, p =.04; STAI-Trait: F1, 67 =7.687, p <.01), but not for Mindfulness (F1, 67 =2.256, p =.14) nor PSAS-somatic. No significant group by time interactions were found. We observed a correlation between PSQI decreases and FFMQ increases in MBTI (r=-.53, p<.01), but not in SHEEP (r=-.07, p=.70) participants. ANCOVA of 6-month PSQI data revealed a significant group by time interaction (F1, 24 =19.525, p =.03), with reduction from baseline in MBTI ( t 12=4.769, p <.01), but not in SHEEP group ( t 12=3.813, p =.08). Conclusion: Preliminary results support MBTI as an accessible but effective behavioural intervention with potential long-term benefits for improving sleep and mood, and reducing cognitive-emotional arousal in the elderly. Support: This study was supported by an award from the 7 th grant call of the Singapore Millennium Foundation Research Grant Programme